Programa nacional de microcrédito produtivo orientado, a gestão de risco social das instituições financeiras e a agenda ESG - Sara Leal Pazzini da Silva (2023)
In this paper, which focus the structures of risk management imposed to the financial institutions (FIs), it was investigated the legal effects produced in the National Program of Productive Oriented Microcredit – Programa Nacional de Microcrédito Produtivo Orientado – (PNMPO), as a result of the adoption of goals related to the social aspect of the agenda Environmental, Social and Governance (ESG) by Brazilian regulation. To this end, the microcredit ecosystem was studied, mapping the purposes of the PNMPO, the subjects involved with it, the contracts entered into and the origin of the resources used. By bibliographical and data analysis, it was proposed that microcredit and ESG together may bring benefits inside and outside Brazil, such as increase in individuals income, improvement of the quality of housing and of the studies of borrowers' families. However, criticisms were also identified. Regarding microcredit, the main criticts are that it may be offered to the social strata that needs it least, may lead to over-indebtedness of borrowers, has an intertwined relationship with political aspects, does not contribute to effective female empowerment, can cause personal problems with the use of the solidarity guarantee, and the fact that the credit agent may act in conflict of interests and entail higher costs for the borrower. ESG is criticized mainly for the fallacious use of its effects in advertising materials. As a result of the investigation carried out, it was found that financial institutions have a duty to identify, measure, evaluate, monitor, report, control and mitigate the risks to which they are subject disclosing the results of these actions. Commercial banks, multiple banks with a commercial portfolio and Caixa Econômica Federal, as obliged to participate in the PNMPO, and other types of FIs, classified by state regulation at levels S1 to S4, which optionally participate in the PNMPO, as they may be subject to the possibility of suffering financial and reputational losses linked to microcredit, must include it in their credit and social risk management structures. The disclosure of this result will only be required from the FIs classified at the S1 level in mid-2023. Thus, despite the fact that when analyzing reports presented by the five largest FIs operating in Brazil (S1) only two of them expressly refer to the to the relationship between the ESG and the PNMPO, it is concluded that the adoption of the ESG brought additional regulatory impositions for the FIs participating in the PNMPO. New researches can verify whether this innovation in state regulation represented an effective improvement in the offer of oriented productive microcredit in Brazil.